The Effect of Fermented Sago Pulp on Performances and Income Over Feed Cost (IOFC) Local Sheep - Mustapa Zahri Ritonga; Hasnudi .; Iskandar Sembiring; Tri Hesti Wahyuni; Nevy Diana Hanafi (Universitas Sumatera Utara, 2018)
This study aims to determine the effect of fermented sago pulp in rations on performance (weight gain, feed consumption, feed conversion) and local sheep's income over feed cost (IOFC). This research was carried out in the community farms of Karang Rejo Village, Stabat District, Langkat Regency. This research started from March to June 2017. The design used was complete randomized design (RAL), with 4 treatment of 5 replications. Each replication consisted of 1 local sheep with an initial weight of 11.05 ± 0.56 kg. The treatment consisted of P1 (50% sago pulp without fermentation + forage), P2 (60% of sago pitch without fermentation + forage), P3 (50% fermented sago pulp + forage), and P4 (60% fermented sago pulp +). The observed variables were performance (body weight gain, feed consumption, feed conversion) and income over feed cost (IOFC). The results showed that the treatment of fermented sago pulp gave a very real effect (P <0.01) on daily weight gain. The mean of P1 = 33,05 g, P2 = 39,95 g, P3 = 46,57 g, P4 = 54,38g. The consumption of fermented sago pulp treatment has a real effect (P <0,01). With average P1 = 486,38 g, P2 = 548,68 g, P3 = 604,69 g, P4 = 671,11 gr. Against the conversion of fermented sago pulp fermentation treatment gave a real effect (P <0.05). With average P1 = 14.78, P2 = 13.90, P3 = 12.99, P4 = 12,49. IOFC the highest local sheep is Rp. 121.568 on treatment of P4 and IOFC lowest at treatment P1 equal to Rp.73.315. The conclusion of the research shows that the utilization of fermented sago pulp can increase body weight gain, feed consumption, local sheep feed conversion. P4 treatment economically has a better economic level than P1,P2 and P3.